ATENUACION DE LA PENA AL RESPONSABLE DEL DELITO TIPIFICADO EN EL ART. 173 DEL CODIGO ORGANICO INTEGRAL PENAL CUANDO UN MENOR INDUCE AL ERROR O ENGAÑO POR MEDIOS ELECTRONICOS. - CORDOVA VELEZ, KELVIN JOSEPH (2016)
This research is framed within the guidelines established by the National University of Loja, the title is "mitigation of punishment THE RESPONSIBLE offense under ART. 173 PENAL CODE organic brown when a minor is misleading or confusing BY ELECTRONIC MEANS "to study the effect of raised me as a general objective, conduct a conceptual, doctrinal and legal study of the Code of Criminal Integral, about crime in which It participates inducing the victim to victimizer error for the illegal act is performed. In order to achieve this goal I use various scientific methods, in the research process, such as: scientific, inductive, deductive, synthetic, etc., as well as apply the survey of 30 lawyers and interview five lawyers; of those who got valuable results like the victim actually if you can participate for the criminal act of running, and therefore punish the offender for a crime that did not commit to the knowledge of the reality of the facts. The fieldwork and the development of this thesis, let me get grounded, clear and precise criteria, very important bibliography provided for verification of the objectives and rationale of the proposed reform to contribute to the changes made. After analyzing all the results, it was deduced, conclusions and recommendations, to finally raise a Law Reform Proposal with which intend to solve the problem.